Preferences an office in commercial administration - Khalil ibrahim Ali; Aday abas Abood (Iraqi Journal of Architecture and Planning, 2009)
This speech resemble the Identity ofArchitecture. A task which makes busy the thinkersand educated class people in general and the Alchitectures in special, on a basic that theIdentity resembles thoughts which are as a kind of eagemess and retuming back for the pasttill the point of resembling, as to be an expression for its role to achieve Identity this researchdeals with through two axis the first relate in describing the dimension and sides ofthereferences in general sight and in Architecture in special sight. The research discusses theArchitecture through explaining the linguistic and Idiomatic dimensions the philosophicalside enlighten this reality and emerge discussions about the material and thoughts which arepreviously the better to limitate the research state from this discussion limited the state whichindicates the complement of the two poles materials and thoughts giving less importance tothebestoneandneglectstheother.Theresearchshiftstotheotherexplanationofthisthought in the Architecture medial and what it means, what is related to it thrcugh thereferences which caused stress for the importance ofthe references role in architecture on onehand and explaining its kinds and branches depending on its relation to the field ofArchitecture and out side and referring to the differences according on it period or age andcercumestances which makes it to depend on the other hand what's above has its importancein dehning the references and it differs from it in being a collective thought due to the triballyseen not having it collectively that means consisting the references in one of its sides due towhat is previously not announcing the references in their collectively pictures the researchindicates the role of references in achieving the Identity through depending on the association'It means achieving a kind of connecting with the cultural and civilization heretic and thenational roots in their in their indicates the importance of references and its necessity inachieving the Identity and indicating a smart and creative beheviour in the presence ofreferences not meaning it to reduce it simportance to the hibal state or shifting it to thehistorical relations and become as ash through analyzing the reality of now a daysArchitecture. In addition to the explanation ofhow to behave with references in the frame ofachieving the Architecture have Identity'